Usefulness of an ultrathin endoscope in esophageal endoscopic submucosal dissection - Kikuchi, Daisuke; Suzuki, Yugo; Kawai, Yusuke; Nomura, Kosuke; Ochiai, Yorinari; Hayasaka, Junnosuke; Mitsunaga, Yutaka; Okamura, Takayuki; Odagiri, Hiroyuki; Yamashita, Satoshi; Matsui, Akira; Tanaka, Masami; Hoteya, Shu (Endoscopy International Open, 2024)
Background and study aims Endoscopic submucosal dissection (ESD) is sometimes challenging because of stenosis and scarring. We examined the use of an ultrathin endoscope for esophageal ESD, which is difficult using conventional endoscopes.Patients and methods A designated transparent hood and ESD knife for ultrathin endoscopes have been developed and clinically introduced. Esophageal ESD was performed on 303 lesions in 220 patients in our hospital from February 2021 to February 2023. Of them, an ultrathin endoscope was used on 26 lesions in 23 cases. The safety and utility of an ultrathin endoscope in esophageal ESD were retrospectively verified.Results All 26 lesions were resected en bloc, and serious complications such as perforation, massive bleeding, or pneumonia, were not observed. Lesions were found on the anal side of the stenosis and over the scarring in 38.6% (10/26) and 50% (13/26) of participants, respectively. Moreover, 46.2% of participants (12/26) had lesions on the cervical esophagus. The total procedure time was 64.1 ± 37.7 minutes, but the average time from oral incision to pocket creation was 121.2 ± 109.9 seconds.Conclusions Ultrathin endoscopes may be useful for difficult esophageal ESD.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Pediatric endoscopy; Benign strictures